n Studie van die invloed van pershout op die trek van hout van Pinus Radiata D. Don. - Du Toit, A. J.(Albertus Johannes) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (D. Sc.) -- Universiteit van Stellenbosch, 1959.